Football Sports Activities Related to the Menstrual Cycle in North Sumatra PON Female Athletes in 2024 - Margolang, Raja Khatulistiwa; Sinaga, Rahmanita (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: Menstruation is the regular discharge of blood from the uterus, which signals the entry of a woman into puberty. Hormonal imbalances in the female reproductive system can lead to menstrual cycle disorders, such as amenorrhea, hypermenorrhea, hypomenorrhea, polymenorrhea, and oligomenorrhea. These disorders can be influenced by various factors, including pathological conditions, psychological conditions, lifestyle, and physical activity. It is reported that 80% of women worldwide experience menstrual cycle disruptions. Among various physical activities, soccer is associated with menstrual cycle disruptions, and it is important to understand the relationship between soccer activities and the menstrual cycle in female athletes. This study uses an analytical descriptive research method with a cross-sectional approach. The study found that 83.30% of athletes reported normal menstrual cycles, while 16.70% experienced abnormal cycles. The majority of athletes engage significantly in football training, with 53.30% training for more than 60 minutes daily and 60.00% participating in weight training more than five times a week. The study also revealed a significant link between football activity and menstrual cycles in athletes. The study also revealed a significant link between football activity and menstrual cycles in athletes.